Modulation of similarity on the distraction resistance of visual working memory representation. (17th July 2022) - Sun, Yanliang; Wang, Lixue; Sun, Nana; Li, Shouxin
Abstract: Controversy exists regarding the distraction resistance of priority items in visual working memory (VWM). The protection account proposes that high‐priority items resist distraction more than low‐priority items, while the vulnerability account proposes that distractors impair high‐priority items more. We proposed another available resource threshold account: distraction will not impair items if available resources exceed their threshold needed for sufficient processing. Using a change‐detection paradigm, we manipulated item priority by color similarity and inserted distractors during VWM retention. We investigated the effect of similarity on distraction resistance of relevant (color) and irrelevant (shape) feature representations (Experiments 1–2), and the neural mechanism of this effect using event‐related potentials (ERPs; Experiment 3). Behavioral results showed distractors impaired the accuracy of dissimilar items when relevant features were memorized and of similar items when irrelevant features were memorized under simultaneous presentation of similar and dissimilar items. Moreover, distractors impaired the accuracy of dissimilar items when relevant features were memorized and of both similar and dissimilar items when irrelevant features were memorized under separate presentation of items. ERP results showed a smaller negative slow wave and P2 but larger N2 under the similar condition. Similarity protected relevant features of similar items against distraction by reducing memory load, decreasing attentional resources allocated to distractors, and strengthening inhibition of distractors. However, similarity did not protect irrelevant features of similar items. Our results support the available resource threshold account, suggesting that VWM is a flexible and intelligent system despite its limited capacity. Abstract : To reconcile the controversy over distraction resistance of high‐priority items in visual working memory, we proposed and provided evidence for an available resource threshold account. This account claims that the distraction resistance of high‐priority items depends on whether available resources of the items exceed the required resource threshold needed for their sufficient processing or not.